The Effects of Airway Pressure Release Ventilation on Pulmonary Permeability in Severe Acute Respiratory Distress Syndrome Pig Models - Cheng, Jiangli; Yang, Jing; Ma, Aijia; Dong, Meiling; Yang, Jie; Wang, Peng; Xue, Yang; Zhou, Yongfang; Kang, Yan (Frontiers in Physiology, 2022)
Objective To compare the effects of APRV and LTV ventilation on pulmonary permeability in severe ARDS. Methods Mini Bama adult pigs were randomized into APRV group (n = 5) and LTV group (n = 5). Severe ARDS animal model was induced by the whole lung saline lavage. Pigs were ventilated and monitored continuously for 48 hours. Results Compared with the LTVV group, Cstat was significantly better (P<0.05) and PaO2/FiO2 ratio showed a trend to be higher throughout the period of experiment in APRV group. Extravascular lung water index and pulmonary vascular permeability index showed a trend to be lower in APRV group. APRV also significantly mitigate lung histopathologic injury determined by the lung histopathological injury score (P<0.05) and gross pathological changes of lung tissues. The protein content of Occludin (P<0.05), claudin-5 (P<0.05), E-cadherin (P<0.05) and VE-cadherin (P<0.05) in the middle lobe of the right lung were higher in the APRV group than in LTV group, among them the content of Occludin (P<0.05) and E-cadherin (P<0.05) of the whole lung was higher in the APRV group. Transmission electron microscopy showed that alveolar-capillary barrier damage was more severe in the middle lobe of lung in LTV group. Conclusion In comparison with LTV, APRV could preserve the alveolar-capillary barrier architecture, mitigate lung histopathologic injury, increase the expression of cell junction protein, improve respiratory system compliance, and showed a trend to reduce extravascular lung water and improve oxygenation. These findings indicated that APRV might led to more profound beneficial effects on integrity of the alveolar-capillary barrier architecture and on expression of biomarkers related to pulmonary permeability.